Enhancement of primary treatment process for domestic wastewater using tannin-based coagulant - Hameed, Yasir Talib (2017)
Coagulation and flocculation as a pre-treatment before biological process is one of the options to enhance the treated water quality and drive possible savings in the construction and operation of treatment plants. The common coagulants such as Al3+ and Fe3+ have been used extensively for long time. However, they are known to act as an additional burden to the environment. Furthermore, there is a public health risk from the use of Al3+. Because of that, great efforts have been made to provide environmentally friendly alternatives to conventional coagulants and flocculants. One of these alternatives is a tannin-based coagulant and flocculant with the name Tanfloc. The aim of this study was to improve the performance of a biofilm process by pretreating the wastewater using Tanfloc and to study the effect of extended use of Tanfloc on the microbial community of the biofilm. To achieve these objectives, a five-stage experiment was conducted. In the first stage, chemical characteristics of Tanfloc were determined using FTIR and EDX in addition to determination of Tanfloc biodegradability. Moreover, jar test experiments were conducted to compare the performance of Tanfloc to Polyaluminium chloride (PAC). In the second stage, a preliminary study was conducted on Tanfloc performance in a continuous flow experiment using only flocculation and sedimentation units. In the third stage, the biofilm unit in the continuous flow experiment was run and Tanfloc effects were evaluated on the three units. Flocculation process was evaluated by studying floc size and residual turbidity. Primary clarifier was evaluated by determining the removal efficiencies. Finally, aeration tank was evaluated by studying treatment efficiency and dissolved oxygen level. When third stage has finished, results were analysed and they were not clear to show the effect of Tanfloc. Consequently, fourth stage using a smaller aeration tank has been decided to be conducted. In the fifth stage, the effect of Tanfloc on the biofilm community was investigated in a specific study of biofilm characteristics. Effect of Tanfloc on the percentage of bacterial genera was studied in addition to substrate concentration and dissolved oxygen. The outcomes of the first stage showed that Tanfloc can compete with PAC as a flocculant. While Tanfloc achieved 85%, 60% and 64% removal efficiencies for TSS, BOD5 and COD, the efficiencies were 64%, 55% and 55% for PAC. The improvement in floc size for Tanfloc compared to PAC improved turbidity removal, Tanfloc removed 70% of the turbidity within only 2 minutes, compared to 42% for PAC. The outcomes of the third and fourth stage showed that even at short flocculation time (7.5 min), Tanfloc showed a high potential to form big flocs with a size distribution of d (10), d (50) and d (90) of 18, 42 and 96 micron. Enhancement of the clarification process due to Tanfloc application was very clear and while the efficiency of TSS removal in the clarifier was only 4% at a flow of 18 L/min (HRT = 55.5 min), with Tanfloc it achieved a 60% efficiency. Even at a high flow of 26 L/min (HRT= 39 min), a removal efficiency of 31% was achieved when Tanfloc was applied. An enhancement in aeration tank performance was noticed due to Tanfloc’s effect on reducing the organic load; the BOD5 for the treated water dropped from the range of 24 – 50 to the range of 7–24 mg/L when Tanfloc was introduced. Moreover, the dissolved oxygen level in the aeration tank jumped almost to double the value when Tanfloc was introduced to the biological process. An interesting point in the results of the fifth stage is the ammonia nitrogen removal. In the experiment without Tanfloc, there was a complete inhibition of ammonia nitrogen removal at retention time of 4 hours, while Tanfloc produced a removal efficiency of around 70% of the ammonia nitrogen at the same retention time (4 hours). Biofilm community analysis showed a significant increment in the percentage of Nitrosomonas and Nitrospira genera in the biofilm cultured by flocculated water (3.33% and 7.8% respectively) compared to the biofilm cultured by raw wastewater (0.073% and 0.19 % respectively). This increase justified and confirmed the aforementioned improvement in ammonia nitrogen removal in the experiment with Tanfloc. The aforementioned results suggest Tanfloc as a promising agent to enhance the performance of clarification and biological treatment units and consequently reduce the required volumes of treatment units and saving energy. In light of this enhancement, Tanfloc could be used to upgrade the existing treatment plants or design compact treatment units.